A kind of AlN-TiMoCoNb metal ceramic material and its preparation method and application
By using AlN-TiMoCoNb cermet material, the synergistic effect of aluminum nitride and TiMoCoNb alloy is used to solve the problem of vulnerability of components during aluminum smelting, the excellent mechanical properties of the material and good corrosion resistance of the melt aluminum are achieved, and the production efficiency and product quality are improved.
Patent Information
- Application Number
- CN202211617914.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-15
AI Technical Summary
During aluminum smelting, die casting and hot dip plating, due to the high corrosion of aluminum melt and the erosion speed and pressure during processing, vulnerable parts are frequently replaced, which affects production efficiency and safety. The dissolution of materials and corrosion products reduces the quality of aluminum liquid, resulting in a decline in product quality.
The AlN-TiMoCoNb cermet material is used, which uses aluminum nitride as the hard phase and TiMoCoNb alloy as the bonded phase, and is prepared by ball milling and discharge plasma sintering processes to control the mass fraction of the bonded phase between 10%-40%, preferably 10-30%.
This material has excellent mechanical properties and good corrosion resistance of fused aluminum. Its microhardness is between 1193HV3 and 1655HV3 and its fracture toughness is 5.12 to 5.83MPa·m1/2. It can be sintered at a lower temperature and is suitable for fused aluminum corrosion materials.
Smart Images

Figure CN116219251B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal ceramic material preparation, and specifically relates to an AlN-TiMoCoNb metal ceramic material and a preparation method and application thereof. Background Art
[0002] Aluminum and its alloys are widely used in transportation, energy, electronics and other fields. In addition to being widely used in structural components, hot-dip aluminum is widely used as an effective steel protection process. However, during the smelting, die-casting and hot-dip plating of aluminum, due to the high corrosiveness of the aluminum melt and the large erosion rate and pressure during the processing, the parts in direct contact with the aluminum melt are very easy to fail. Frequent replacement of vulnerable parts greatly affects production efficiency and production safety. At the same time, the dissolution of materials and corrosion products reduces the quality of aluminum liquid, resulting in a decline in product quality. Therefore, improving the material's resistance to molten aluminum corrosion is of great significance to improving product quality and production efficiency. Summary of the invention
[0003] In view of the shortcomings of the prior art, the first object of the present invention is to provide an aluminum nitride-based metal ceramic material. The AlN-TiMoCoNb metal ceramic material provided by the present invention has both excellent mechanical properties and good resistance to molten aluminum corrosion.
[0004] The second object of the present invention is to provide a method for preparing an AlN-TiMoCoNb metal ceramic material.
[0005] The third object of the present invention is to provide an application of AlN-TiMoCoNb metal ceramic material.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an AlN-TiMoCoNb metal ceramic material. The AlN-TiMoCoNb metal ceramic material uses AlN as a hard phase and a TiMoCoNb alloy as a bonding phase, wherein the mass fraction of the TiMoCoNb alloy in the metal ceramic material is 10%-40%, preferably 10-30%.
[0008] The AlN-TiMoCoNb metal ceramic material provided by the present invention has aluminum nitride as a hard phase and TiMoCoNb alloy as a bonding phase, wherein AlN has good corrosion resistance to molten aluminum and hardness. At the same time, aluminum nitride has good thermal conductivity and low thermal expansion coefficient, but AlN, as a covalent compound, has poor sintering properties and poor wettability with most metals. The inventors found that Ti, Nb, and Co form nitrides with AlN to enhance wettability with the ceramic matrix; Nb and Co elements show better thermal mechanical fatigue resistance than Ni-based alloys and tool steels in molten aluminum, while Ti and Mo elements have good compatibility with aluminum nitride, similar thermal expansion coefficients and good adhesion at high temperatures, which can enhance the metal ceramic material, and Ti, Mo, Co, and Nb all have good corrosion resistance to molten aluminum; under the synergistic effect of each metal in the bonding phase and the AlN matrix, the obtained metal ceramic material has both excellent mechanical properties and good corrosion resistance to molten aluminum.
[0009] In the present invention, the selection of the composition of the bonding phase is very important. If the selection of the bonding phase is unreasonable, the bonding phase and the ceramic matrix will have poor bonding, which will affect the molding and fail to enhance the mechanical properties. If the selected bonding phase itself has poor molten aluminum corrosion resistance, the aluminum liquid will easily corrode the bonding phase first, thereby reducing the overall molten aluminum corrosion resistance of the metal ceramic.
[0010] In addition, the ratio of the bonding phase is controlled within the scope of the present invention to achieve excellent performance. If the bonding phase is too little, the hardness and fracture toughness of the ceramic will be affected, and pure AlN will directly explode when in contact with molten aluminum; too much bonding phase will affect the hardness and fracture toughness of the ceramic, and will affect the corrosion resistance of the ceramic in molten aluminum during long-term corrosion.
[0011] In a preferred embodiment, the AlN-TiMoCoNb metal ceramic material has the following composition by mass percentage: AlN: 70-90%, Ti: 1.62-6.48%, Mo: 3.25-12.98%, Co: 1.99-7.97%, and Nb: 3.14-12.57%.
[0012] The inventors have found that by controlling the ratio of the components within the above range, the performance of the final metal ceramic material is optimal. For example, Ti and Co will react with AlN to generate TiN and CoN, thereby strengthening the metal ceramic material. However, excessive amounts will affect the corrosion resistance of the composite material itself. Al and Mo have good adhesion and no secondary chemical reaction products, thus playing a similar role of second phase toughening. At the same time, Mo itself has good resistance to molten aluminum corrosion.
[0013] In a preferred embodiment, the AlN-TiMoCoNb metal ceramic material has a microhardness of 1193HV3 to 1655HV3 and a fracture toughness of 5.12 to 5.83MPa·m 1 / 2 .
[0014] The present invention also provides a method for preparing an AlN-TiMoCoNb metal ceramic material, comprising: performing ball milling on AlN powder, titanium powder, molybdenum powder, cobalt powder and niobium powder to obtain a mixed powder, and performing spark plasma sintering on the mixed powder to obtain the AlN-TiMoCoNb metal ceramic material, wherein the spark plasma sintering temperature is 1650-1750°C.
[0015] The AlN-TiMoCoNb metal ceramic material of the present invention is prepared by ball-milling and activating AlN powder, titanium powder, molybdenum powder, cobalt powder and niobium powder, and then sintering the metal ceramic material at a relatively low temperature through spark plasma sintering to obtain a metal ceramic material with excellent performance. The inventor unexpectedly discovered that due to the high hardness of AlN, the present invention directly blends titanium powder, molybdenum powder, cobalt powder and niobium powder with AlN powder to achieve mechanical alloying, and finally adopts spark plasma sintering to obtain an AlN-TiMoCoNb metal ceramic material with uniform composition.
[0016] In a preferred embodiment, the purity of the titanium powder, molybdenum powder, cobalt powder and niobium powder is greater than 99.9%, and the particle size is less than 10 μm.
[0017] In a preferred embodiment, the ball milling method is wet ball milling, the rotation speed of the wet ball milling is 200-300 r / min, the wet ball milling time is 3-24 h, the ball-to-material ratio is 3-5:1, and the process control agent of the wet ball milling is anhydrous ethanol.
[0018] The inventors found that by controlling the ball milling parameters within the above range, the performance of the metal ceramic material finally obtained is optimal. The ball milling speed and time affect the energy of the powder. A lower speed or a shorter time will affect the formation of the sintered product. If the ball-to-material ratio is too low, the collision efficiency between the grinding balls and the powder particles will be reduced, which will reduce the powder mixing efficiency. If the ball-to-material ratio is too high, the probability of collision between the grinding balls will increase and the collision frequency between the grinding balls and the powder will be reduced, which is not conducive to powder mixing.
[0019] In a preferred embodiment, the mixed powder is dried at 70-90° C. for 8-12 hours under a vacuum degree of -0.08 MPa to -0.1 MPa, and then spark plasma sintering is performed.
[0020] In a preferred embodiment, the spark plasma sintering has a heating rate of 50-200° C. / min, a holding time of 5-10 min, and a pressure of 50-60 MPa.
[0021] Further preferably, during the spark plasma sintering process, the temperature is first increased to 700°C at a heating rate of 100-200°C / min to increase the pressure to 18-20MPa, then increased to 1600°C at a heating rate of 100-200°C / min to increase the pressure to 40-49MPa, and then increased to 1650-1750°C at a heating rate of 50-70°C / min for sintering, and kept warm for 5-10min, with the pressure controlled at 50-60MPa.
[0022] The present invention also provides an application of an AlN-TiMoCoNb metal ceramic material, wherein the AlN-TiMoCoNb metal ceramic material is used as a molten aluminum corrosion resistant material.
[0023] Principles and advantages
[0024] The present invention provides an AlN-TiMoCoNb metal ceramic material, wherein the AlN-TiMoCoNb metal ceramic material uses AlN as a hard phase and a TiMoCoNb alloy as a bonding phase. Aluminum nitride theoretically has good resistance to molten aluminum corrosion and hardness. At the same time, aluminum nitride has good thermal conductivity and a low thermal expansion coefficient, and theoretically has good thermal shock resistance. However, aluminum nitride has low toughness, a melting point of nearly 2000°C, and poor sintering properties. Therefore, a metal with good wettability is selected as a bonding phase, and the excellent toughness and low melting point of the metal bonding phase are used to improve the shortcomings of aluminum nitride, such as poor toughness and difficulty in sintering. The present invention uses Ti, Mo, Co and Nb to form nitrides with AlN to enhance wettability with a ceramic matrix; Nb and Co elements show better thermal mechanical fatigue resistance in molten aluminum than Ni-based alloys and tool steels, and Ti and Mo elements have good compatibility with aluminum nitride, similar thermal expansion coefficients and good adhesion at high temperatures, and can enhance metal ceramic materials. At the same time, Ti, Mo, Co and Nb all have good corrosion resistance to molten aluminum; under the synergistic effect of the metals in the bonding phase and the AlN matrix, the obtained metal ceramic material has both excellent mechanical properties and good corrosion resistance to molten aluminum.
[0025] The preparation method of the present invention can sinter the metal ceramic material at a lower temperature by ball-milling and activating AlN powder, titanium powder, molybdenum powder, cobalt powder and niobium powder, and then sintering the metal ceramic material by spark plasma sintering, thereby obtaining the metal ceramic material with excellent performance.
[0026] The present invention improves the sintering performance of ceramics by adding a metal bonding phase, and spark plasma sintering can significantly reduce the sintering temperature and sintering time, and has the characteristics of rapidity and high efficiency.
[0027] The method of the invention is easy to operate, the equipment used is commonly seen, the materials are easy to obtain, and it is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a microscopic SEM image of the AlN-TiMoCoNb metal ceramic monolithic material in Example 1 of the present invention.
[0029] Figure 2 This is a microscopic SEM image of the AlN-TiMoCoNb metal ceramic monolithic material in Example 2 of the present invention.
[0030] Figure 3 This is a microscopic SEM image of the AlN-TiMoCoNb metal ceramic monolithic material in Example 3 of the present invention.
[0031] Figure 4 The graph is a graph showing the variation of corrosion thickness of metal ceramic materials over time in two examples of the present invention.
[0032] Figure 5 The graph is a graph showing the change in thickness of metal ceramic material loss over time in two examples of the present invention.
[0033] Figure 6 These are SEM images of the corrosion interface of the material in Example 2 of the present invention after being corroded in 700° C. aluminum liquid for 2, 4, 8, 20, and 40 days. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described below in conjunction with the accompanying drawings in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The scope of protection of the present invention is not limited to a specific embodiment.
[0035] Embodiment 1:
[0036] The invention discloses a metal ceramic material with a chemical formula of AlN-TiMoCoNb and resistant to molten aluminum corrosion and a preparation method thereof.
[0037] (1) Sampling: Weigh aluminum nitride powder, titanium powder, molybdenum powder, cobalt powder, and niobium powder according to the following mass percentages: aluminum nitride powder: 70%, titanium powder: 4.86%, molybdenum powder: 9.74%, cobalt powder: 5.98%, and niobium powder: 9.43%.
[0038] (2) Ball milling: Place the weighed mixture into a ball mill, and weigh the required grinding balls according to the mass ratio of balls to mixed powder of 3:1 and place them into the ball mill. Use wet ball milling process, and then pour an appropriate amount of anhydrous ethanol into the ball mill to cover the powder. The ball mill speed is 300r / min, and the ball milling time is 3 hours.
[0039] (3) Drying: The ball-milled mixture is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 70-90°C and a vacuum degree of -0.1 MPa.
[0040] (4) Sintering: The dried powder is taken out and placed in a cylindrical graphite mold, and then placed in a sintering device for sintering. The sintering process is set as follows: the temperature is increased to 1700°C at a rate of 100°C / min, and the temperature is kept at this temperature for 10 minutes. The sintering pressure is 60MPa. After sintering, the powder is cooled in the furnace and then demolded to obtain the sample. Figure 2 The microscopic morphology of the sample under scanning electron microscope (SEM).
[0041] The prepared samples were cut into 4×5×10mm rectangular specimens using a precision cutting machine, and 5 specimens were cut. The surface of the specimens was polished with sandpaper to remove the oxide film on the surface of the specimens. The thickness of the specimens before corrosion was measured using a micrometer, and then the specimens were placed in a graphite crucible filled with 700°C aluminum liquid for corrosion experiments. The specimens were heated and kept warm using a well-type resistance furnace, and were taken out after being corroded for 2, 4, 6, 8, and 10 days, respectively. The microstructure of the corrosion interface was analyzed using a scanning electron microscope (SEM), and the chemical composition of the phase was determined using an energy dispersive spectrometer (EDS).
[0042] Calculate the corrosion depth and corrosion rate of the sample at different times. This experiment uses the depth method to measure the corrosion rate, and the calculation formula is: v = (ab) / 2t.
[0043] Where a is the thickness of the sample before corrosion, b is the thickness of the sample after corrosion, and t is the corrosion time. Before the corrosion experiment, the thickness a before corrosion was accurately measured with a micrometer, and then the cross-section of the sample after corrosion was observed under a scanning electron microscope, and the remaining thickness b of the sample after corrosion was measured using Smile View software.
[0044] The Vickers hardness of the sample is 1520.5HV3 and the fracture toughness is 5.12MPa m 1 / 2 .
[0045] Embodiment 2:
[0046] The invention discloses a metal ceramic material with a chemical formula of AlN-TiMoCoNb and resistant to molten aluminum corrosion and a preparation method thereof.
[0047] Step (1): weigh AlN, Ti, Mo, Co, and Ni powders according to the following mass percentages: aluminum nitride powder: 80%, titanium powder: 3.24%, molybdenum powder: 6.49%, cobalt powder: 3.99%, and niobium powder: 6.28%.
[0048] (2) Ball milling: Place the weighed mixture into a ball mill, and weigh the required grinding balls according to the mass ratio of balls to mixed powder of 3:1 and place them into the ball mill. Use wet ball milling process, and then pour an appropriate amount of anhydrous ethanol into the ball mill to cover the powder. The ball mill speed is 300r / min, and the ball milling time is 3 hours.
[0049] (3) Drying: The ball-milled mixture is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 70-90°C and a vacuum degree of -0.1 MPa.
[0050] (4) Sintering: Take out the dried powder, put it into a cylindrical graphite mold, and then put it into a sintering equipment for sintering. The sintering process is set as follows: heat up to 700℃ at a heating rate of 100℃ / min, increase the pressure to 19MPa, then heat up to 1600℃ at a heating rate of 100℃ / min, increase the pressure to 47MPa, and then heat up to 1700℃ at a heating rate of 50℃ / min for sintering, increase the pressure to 60MPa, keep at 1700℃ for 10min, and control the pressure to 60MPa. After sintering, cool it in the furnace and then demold it to obtain the sample. Figure 2 The microscopic morphology of the sample under scanning electron microscope (SEM).
[0051] The prepared samples were cut into 4×5×10mm rectangular specimens using a precision cutting machine, and 5 specimens were cut. The surface of the specimens was polished with sandpaper to remove the oxide film on the surface of the specimens. The thickness of the specimens before corrosion was measured using a micrometer, and then the specimens were placed in a graphite crucible filled with 700°C aluminum liquid for corrosion experiments. The specimens were heated and kept warm using a well-type resistance furnace, and were taken out after being corroded for 2, 4, 6, 8, and 10 days, respectively. The microstructure of the corrosion interface was analyzed using a scanning electron microscope (SEM), and the chemical composition of the phase was determined using an energy dispersive spectrometer (EDS).
[0052] Calculate the corrosion depth and corrosion rate of the sample at different times. This experiment uses the depth method to measure the corrosion rate, and the calculation formula is: v = (ab) / 2t.
[0053] Where a is the thickness of the sample before corrosion, b is the thickness of the sample after corrosion, and t is the corrosion time. Before the corrosion experiment, the thickness a before corrosion was accurately measured with a micrometer, and then the cross-section of the sample after corrosion was observed under a scanning electron microscope, and the remaining thickness b of the sample after corrosion was measured using Smile View software.
[0054] The Vickers hardness of the sample is 1655.5HV3 and the fracture toughness is 5.83MPa m 1 / 2 .
[0055] Table 1 shows the average corrosion thickness rate of the metal ceramic material in two examples of the present invention.
[0056] Table 1
[0057]
[0058] Embodiment 3:
[0059] The invention discloses a metal ceramic material with a chemical formula of AlN-TiMoCoNb and resistant to molten aluminum corrosion and a preparation method thereof.
[0060] Step (1): weigh AlN, Ti, Mo, Co, and Ni powders according to the following mass percentages: aluminum nitride powder: 90%, titanium powder: 1.62%, molybdenum powder: 3.25%, cobalt powder: 1.99%, and niobium powder: 3.14%.
[0061] (2) Ball milling: Place the weighed mixture into a ball mill, and weigh the required grinding balls according to the mass ratio of balls to mixed powder of 3:1 and place them into the ball mill. Use wet ball milling process, and then pour an appropriate amount of anhydrous ethanol into the ball mill to cover the powder. The ball mill speed is 300r / min, and the ball milling time is 3 hours.
[0062] (3) Drying: The ball-milled mixture is placed in a vacuum drying oven and dried for 12 hours at a drying temperature of 70-90°C and a vacuum degree of -0.1 MPa.
[0063] (4) Sintering: The dried powder is taken out and placed in a cylindrical graphite mold, and then placed in a sintering device for sintering. The sintering process is set as follows: the temperature is increased to 1700°C at a rate of 100°C / min, and the temperature is kept at this temperature for 10 minutes. The sintering pressure is 60MPa. After sintering, the powder is cooled in the furnace and then demolded to obtain the sample. Figure 2 The microscopic morphology of the sample under scanning electron microscope (SEM).
[0064] The prepared samples were cut into 4×5×10mm rectangular specimens using a precision cutting machine, and 5 specimens were cut. The surface of the specimens was polished with sandpaper to remove the oxide film on the surface of the specimens. The thickness of the specimens before corrosion was measured using a micrometer, and then the specimens were placed in a graphite crucible filled with 700°C aluminum liquid for corrosion experiments. The specimens were heated and kept warm using a well-type resistance furnace, and were taken out after being corroded for 2, 4, 6, 8, and 10 days, respectively. The microstructure of the corrosion interface was analyzed using a scanning electron microscope (SEM), and the chemical composition of the phase was determined using an energy dispersive spectrometer (EDS).
[0065] Calculate the corrosion depth and corrosion rate of the sample at different times. This experiment uses the depth method to measure the corrosion rate, and the calculation formula is: v = (ab) / 2t.
[0066] Where a is the thickness of the sample before corrosion, b is the thickness of the sample after corrosion, and t is the corrosion time. Before the corrosion experiment, the thickness a before corrosion was accurately measured with a micrometer, and then the cross-section of the sample after corrosion was observed under a scanning electron microscope, and the remaining thickness b of the sample after corrosion was measured using Smile View software.
[0067] The Vickers hardness of the sample is 1193.7HV3 and the fracture toughness is 5.47MPa m 1 / 2 .
[0068] Comparative Example 1:
[0069] The other conditions are the same as those in Example 2, except that the sintering temperature is increased to 1800°C. Obvious stratification can be seen from the sample interface, and the hardness drops to about 700 HV3. At the same time, it corrodes into a loose and porous structure in just 2 days in the aluminum liquid, and can easily turn into fine particles under the action of external force.
[0070] Comparative Example 2
[0071] The other conditions are the same as those in Example 2, except that Ti is removed. It can be found that the temperature required for sintering increases and the hardness decreases. At the same time, the sample cracks after short-term corrosion in the aluminum liquid, and in severe cases, local powdery shedding occurs.
[0072] Comparative Example 3
[0073] The other conditions are the same as those in Example 2, but only Nb is removed. It can be found that the mechanical properties of the sintered sample decrease, which indicates that Nb reacts with AlN to form NbN and NbAl3, improving the bonding between the binder phase and the matrix ceramic.
[0074] The embodiments are only for facilitating the understanding of the technical solutions of the present invention and do not constitute a limitation on the protection scope of the present invention. Any simple modifications, equivalent changes and modifications made to the above solutions that do not depart from the content of the technical solutions of the present invention or are based on the technical essence of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing an AlN-TiMoCoNb metal ceramic material, characterized in that: AlN powder, titanium powder, molybdenum powder, cobalt powder and niobium powder are ball-milled to obtain a mixed powder, and the mixed powder is subjected to spark plasma sintering to obtain AlN-TiMoCoNb metal ceramic material, wherein the temperature of the spark plasma sintering is 1650-1750° C.; The AlN-TiMoCoNb metal ceramic material has AlN as a hard phase and TiMoCoNb alloy as a bonding phase, wherein the mass fraction of the TiMoCoNb alloy in the metal ceramic material is 10%-40%; The AlN-TiMoCoNb metal ceramic material has the following composition by mass percentage: AlN: 70-90%, Ti: 1.62-6.48%, Mo: 3.25-12.98%, Co: 1.99-7.97%, and Nb: 3.14-12.57%.
2. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: The purity of the titanium powder, molybdenum powder, cobalt powder and niobium powder is all greater than 99.9%, and the particle size is all less than 10 μm.
3. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: The ball milling method is wet ball milling, the rotation speed of the wet ball milling is 200-300r / min, the wet ball milling time is 3-24h, the ball-to-material ratio is 3-5:1, and the process control agent of the wet ball milling is anhydrous ethanol.
4. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: The mixed powder is dried at 70-90° C. for 8-12 hours under a vacuum degree of -0.08 MPa to -0.1 MPa, and then spark plasma sintering is performed.
5. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: The spark plasma sintering has a heating rate of 50-200° C. / min, a heat preservation time of 5-10 min, and a pressure of 50-60 MPa.
6. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: During the spark plasma sintering process, the temperature is first raised to 700°C at a heating rate of 100-200°C / min to increase the pressure to 18-20MPa, then raised to 1600°C at a heating rate of 100-200°C / min to increase the pressure to 40-49MPa, and then raised to 1650-1750°C at a heating rate of 50-70°C / min for sintering, and the pressure is controlled at 50-60MPa.
7. The method for preparing an AlN-TiMoCoNb metal ceramic material according to claim 1, characterized in that: The AlN-TiMoCoNb metal ceramic material has a microhardness of 1193HV3 to 1655HV3 and a fracture toughness of 5.12 to 5.83MPa·m 1 / 2 .
8. Application of an AlN-TiMoCoNb metal ceramic material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The AlN-TiMoCoNb metal ceramic material is used as a molten aluminum corrosion resistant material.
Citation Information
Patent Citations
Preparation method of aluminum nitride-based cermet material
CN109136610A